Three Italian Illuminated Cuttings in the Royal Library of Copenhagen: the Master B. F., Attavante and the Master of Montepulciano Gradual I - Mattia, Eleonora (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2017)
Eleonora Mattia: Three Italian illuminated Cuttings in the Royal Library of Copenhagen Some observations on the history of collecting illuminated cuttings serve to introduce three unpublished Italian fragments that are part of a collection of illuminated fragments conserved in the Royal Danish Library. The miniatures are described from the point of view of their liturgical and art-historical content and are presented in the form of entries in a catalogue raisonné. The Master B. F., who grew up under the shadow of Leonardo de Vinci, was among those miniaturists most sought-after by collectors in the late nineteenth and early twentieth century because of his evident stylistic debts to the great painter. The beautiful miniature in Copenhagen can now be added to the other known works of this Master and is critical not only to the reconstruction of his corpus, but also for the history of collecting, as it comes from the prestigious Holford Collection. It was already correctly attributed when it entered the collection of the Royal Library; it is here inserted into the activity of the artist, a dating is proposed, and a provenance is suggested from the series of choir books in the monastery of Santi Angelo e Nicolò a Villanova Sillaro in Lombardy, which were broken up around 1799. The Danish cutting here attributed to Attavante has a specific iconography that demonstrates an originality and an independence from models followed by contemporary Florentine painting, qualities not always acknowledged to the well known miniaturist whose extensive figurative production has sometimes been considered repetitive. A third fragment is here attributed to the Pisan Master of Montepulciano Gradual I. This anonymous miniaturist is at the centre of the most recent and innovative studies of fourteenth-century Tuscan painting: his activity belongs to the diversified texture of artistic production between Florence and its nearby cities, with expressive modalities independent of the tradition of the more strictly Giottesque masters. The miniature attributed to him here is to be added to the catalogue of his works, dispersed as they are in many European and American collections.